Treatment of severe hyperbilirubinemia through coupled plasma filtration adsorption - Dambruoso, Pierpaolo; Cappellano, Nicola; Raimondo, Pasquale (Indian Journal of Case Reports, 2018)
The development of severe hyperbilirubinemia after cardiac surgery performed with cardiopulmonary bypass is a possible life-threatening challenging complication because its mechanism is still not completely clarified, and there are only a few specific therapies available for acute hepatobiliary injury. Here, we report the case of an 80-year-old male scheduled for elective aortic valve replacement, during the 1st post-operative day (POD 1), developed acute systo-diastolic cardiac failure, with a severe aortic paravalvular leak. The surgeon decided reoperation to correct prosthesis dehiscence. There was a continuous total serum bilirubin increase, with a peak value of 24.50 mg/dl on POD 16. It was diagnosed as a “cholestatic post-cardiac surgery syndrome,” and we performed seven cycles of coupled plasma filtration adsorption (CPFA), with definitive stable bilirubinemia reduction to 3.0 mg/dl at the discharge. CPFA was found to be a good hemodepurative technique to manage successfully severe hyperbilirubinemia of “cholestatic post-cardiac surgery syndrome.”